Effect of age, sex, and race distance on front crawl stroke parameters in subelite adolescent swimmers during competition - Dormehl, S. J.; Osborough, C. (Pediatric Exercise Science, 2015)
The aims of this study were to determine the effect of age, sex and race distance on velocity (v), stroke rate (SR), stroke length (SL) and stroke index (SI) of subelite adolescent swimmers in competition, and to investigate their pacing strategies during the 100-m and 200-m events. Video footage of 112 adolescent swimmers (56 female; 56 male), competing in the 100-m and 200-m freestyle events, in two age groups (12-14; 15-18 years) was recorded and subsequently analyzed. A MANOVA showed that all stroke parameters significantly differed between sexes and between race distances. The older adolescents had a higher v, a longer SL and a greater SI (p < .01) than the younger adolescents. There were significant interaction effects between age and sex for v, SL and SI. Most adolescents had a SL that was within 7% of that reported for 1992 Olympians, but had up to 16% lower SRs. Separate Friedman`s ANOVAs showed that SL differed between successive race quarters for both age groups, both sexes and both race distances. It is likely that physical immaturity, inexperience in competition pacing and within-race fatigue strongly influence the performances of subelite adolescent front crawl swimmers.